The Effect of Organic Fertilizer Type, Nutrient Composition, and Application Method on Tomato Plant Growth in Plantation Areas in the Cianjur Region of West Java - Jatsiyah, Venti; Safruddin, Safruddin (Westscience Press, 2024)
This study investigated the effect of organic fertilizer type, nutrient composition, and application method on tomato plant growth in the plantation areas of the Cianjur region, West Java. A randomized complete block design (RCBD) with factorial arrangements was employed, and data were collected using Likert scale ratings from 110 tomato plants. The analysis revealed significant differences in plant growth among different organic fertilizer types, with biofertilizers exhibiting the highest mean growth score. Moreover, fertilizers with balanced nutrient compositions resulted in superior plant growth compared to those with imbalanced compositions. Additionally, foliar spraying emerged as the most effective application method, promoting higher plant growth compared to broadcasting and banding methods. These findings highlight the importance of considering organic fertilizer characteristics and application techniques in optimizing tomato plant growth in agricultural systems.